Training and Awarding for Water Clover Processing as a Main Commodity for Leading UMKM in Kampung Semanggi Benowo, Surabaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic that has occurred in Indonesia since March 11, 2020 has had a big impact, especially on the economic sector. One of the important factors of the economy in Indonesia is UMKM. In Surabaya, there are also UMKM affected, that is Leading UMKM of Kampung Semanggi Benowo. Training and Awarding need to be carried out so that these UMKM can survive during this pandemic by processing their main commodity, water clover. Water clover is processed with milkfish so that it can become clover meatballs that have a selling value. After passing the training stage, UMKM participants took part in a competition to boost their competitiveness before competing with other UMKM. Furthermore, participants received awards for their participation during training activities and competitions. This training and awarding activity lasted for two days on 7 and 14 February 2022 and going well. The evaluation of the participants showed the positive impact that many parties had through this activity.